Associations between pesticide mixtures applied near home during pregnancy and early childhood with adolescent behavioral and emotional problems in the CHAMACOS study. Issue 3 (5th June 2021) - Hyland, Carly; Bradshaw, Patrick T.; Gunier, Robert B.; Mora, Ana M.; Kogut, Katherine; Deardorff, Julianna; Sagiv, Sharon K.; Bradman, Asa; Eskenazi, Brenda
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Studies suggest that exposure to pesticides during pregnancy and early childhood is associated with adverse child neurodevelopment. Research to date has focused primarily on exposure to single pesticides or pesticide classes in isolation; there are little data on the effect of exposure to pesticide mixtures on child and adolescent neurodevelopment. Methods: Using California's Pesticide Use Reporting database, we estimated agricultural pesticide use within 1 km of the home during the prenatal and postnatal (ages 0–5 years) periods among participants in the Center for the Health Assessment for Mothers and Children of Salinas (CHAMACOS) birth cohort. We implemented a Bayesian Hierarchical linear mixed-effects model to examine associations with maternal- and youth-reported behavioral and emotional problems from the Behavior Assessment System for Children, 2nd edition (BASC-2) at ages 16 and 18 years (n = 593). Results: We observed mostly null associations between pesticide applications and neurobehavioral outcomes. There were some trends of modestly increased internalizing behaviors and attention problems in association with organophosphate insecticide use near the home during the prenatal period. In the postnatal period, a two-fold increase in glyphosate applications was associated with more youth-reported depression (β = 1.2, 95% credible intervals [CrI] = 0.2, 2.2), maternal-reported internalizing behaviors (β = 1.23, 95% CrI = 0.2, 2.3), and anxiety (β = 1.2, 95% CrI = 0.2, 2.3). We observed some protective associations with imidacloprid during the prenatal period, particularly in sex-specific analyses. Conclusions: We found only some subtle associations between some pesticides and neurobehavioral outcomes. This study extends previous work by considering potential exposure to mixtures of pesticides.